Current Challenges Face By Pakistan R&D Sector In Context Of Innovation Management Capabilities - Zeeshan , Asim; Sorooshian, Shahryar (2017)
As most of the developing countries Pakistan has not yet structure the national innovation system with any concrete policies in order to assist their domestic requirement without comprehensive development of their R&D capabilities. As compares to some of the emerging economies Pakistan National innovation system (NIS) unfortunately operated in isolation unsynchronized structure may cause serious challenge for R&D sector that still unable to developed innovational capabilities. This research study highlights the potential gaps in national innovation structure to facilitate the R&D sector. This research study explore the significance of innovation capabilities as during the development of national innovation policy to support the innovation structure.